PENYELESAIAN SENGKETA EKONOMI SYARIAH MENJADI KEWENANGAN PENGADILAN AGAMA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOM0R 93/PUU-X/2012 - Redi Hadiyanto (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTThis research is motivated by the phenomenon of the Sharia Economic Dispute Settlement which could initially be resolved in a religious court also in the general court. There is no legal certainty. While the legal certainty of each citizen is guaranteed and regulated in the 1945 constitution article 28D paragraph (1), in that article states that the state guarantees the legal certainty of each citizen. The purpose of this study is to understand about the elimination of the explanation of article 55 paragraph 2 of law number 21 years, to reassure the certainty of the law, then law number 21 of 2008 must be tested materially to the Constitutional Court to guarantee the legal certainty of every citizen. The method used in this research is content analysis, namely analyzing the Constitutional Court Decision Number 93 / PUU-X / 2012. In addition, this research also uses sociological and normative-juridical approach. The results showed that the Constitutional Court granted the material test petition submitted by the petitioners, with the result of Constitutional Court decision number 93 / PUU-X / 2012, that the explanation of article 55 paragraph 2 of law number 21 of 2008 was abolished because it did not guarantee the legal certainty of every citizen country. So that after the ruling of the constitutional court is ratified, the Sharia Economic Dispute Settlement case becomes the absolute authority of the religious court, it cannot be processed and decided outside the religious court.Keywords: Sharia Economic Dispute Settlement, Religious Courts